Modified polysulfones. IV. Synthesis and characterization of polymers with silicon substituents for a comparative study of gas-transport properties - Guiver, MD; Robertson, GP; Rowe, S; Foley, S; Kang, YS; Park, HC; Won, J; Thi, HNL (WILEY, 2001)
We previously conducted a detailed study Df gas-transport and other properties of a series of silicon derivatives of Udel polysulfone (PSf) and Radel polyphenylsulfone; we now report the details of their preparation by the reaction of lithiated polymer intermediates with chlorosilylalkylaryl electrophiles. Ortho-sulfone-substituted polymers with pendant tri:methylsilyl, dimethylphenylsilyl, and diphenylmethylsilyl and other groups were obtained by direct metalation followed by the reaction of the dilithiated intermediate with the appropriate silyl electrophile. In addition, the structural regularity and geometry of the dilithiated site was also exploited to introduce silicon into the main chain by the reaction of dichlorosilyl electrophiles, leading to the formation of a new tricyclic heteroatom ring. Ortho-ether PSf derivatives were obtained from a dibrominated polymer via the lithiation of brominated polymer and reaction with a silyl electrophile. The degree of substitution of the silyl groups was 2.0 or less from dilithiated polymers and was dependent on the electrophile reactivity and reaction conditions. A detailed structural characterization of the polymers by NMR and IR spectroscopy is reported in addition to glass-transition temperatures and thermal stabilities. (C) 2001 John Wiley & Sons, Inc.
Keywords: CHEMICAL-MODIFICATION; PERMEABILITY; DERIVATIVES